2019
DOI: 10.25217/igcj.v2i1.310
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Technique within Group Counseling to Reduce Student's Anxiety on Facing Exam

Abstract: The purpose of this study is determine the effectiveness of group counseling model with relaxation technique assisted by instrumental music to reduce students' anxiety on facing exam.  This type of research is quantitative research with quasi-experimental research design, using the initial test design (pretest) and the final treatment (posttest). This research involved PGRI junior high school 1 Palembang students. The steps taken are: 1) preparation of the experimental group, 2) giving the pretest in the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…In educational context, particularly within school environment, many factors that trigger anxiety among students. The high target of learning achievement, competitive climate, solid provision of tasks, and rigorous assessment system are factors that cause anxiety (Arizona, Nurlela, & Jannati, 2019). Several previous studies have found a positive relationship between social anxiety and loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…In educational context, particularly within school environment, many factors that trigger anxiety among students. The high target of learning achievement, competitive climate, solid provision of tasks, and rigorous assessment system are factors that cause anxiety (Arizona, Nurlela, & Jannati, 2019). Several previous studies have found a positive relationship between social anxiety and loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Ketika individu memiliki pikiran yang rasional maka tidak akan terjadi penyimpangan perilaku yang berarti. Teknik relaksasi ini dapat diterapkan pada berbagai macam kecemasan, salah satunya adalah kecemasan yang dimiliki siswa terhadap ujian (Abida et al, 2021;Dahbi, 2015;Larson et al, 2011;Nurlela & Jannati, 2019;Nurnaningsih, 2020). Penerapan relaksasi dan penerapan pada kehidupan sehari-hari akan membantu individu dalam mengondisikan diri agar selalu rileks ketika menghadapi ujian sehingga mereka dapat mempersiapkan maupun mengerjakan ujian dengan tenang serta percaya diri, penerapan relaksasi ini juga mempengaruhi performance mereka ketika mengerjakan ujian, mereka tak akan terganggu, dengan nyaman melaksanakan ujian dan kecil kemungkinan untuk melupakan materi yang telah dipelajari sebelumnya (Juliawati et al, 2019;Nurhidayati & Firmanto, 2017;Nwokolo et al, 2017;Wardiana & Sandhya, 2019) yang akan dilalui yaitu 7 sesi yang terdiri dari 1 sesi pada tahap awal, 5 sesi pada tahap inti dan 1 sesi pada tahap akhir.…”
Section: *Esty Aryani Safithryunclassified
“…Oleh karena itu, penanganan lebih lanjut perlu diberikan dalam upaya mengatasi kecemasan dalam persiapan menghadapi uji kompetensi exit exam. Beberapa penanganan untuk mengurangi kecemasan ujian yaitu guided imagery (Kumari G. et al, 2009), teknik relaksasi (Arizona et al, 2019), konseling profesional untuk identifikasi stres serta penanganan stres (Senarath, 2020).…”
Section: • Tingkat Kecemasan Mahasiswa D3 Rmik Universitas Esa Unggul Dalam Persiapan Menghadapi Uji Kompetensi Exit Examunclassified